Dietary supplementation of nano-selenium improves reproductive performance, sexual behavior and deposition of selenium in the testis and ovary of Japanese quail - kazaz, Sara Elsayed El; Samaha, Magda Ismail Abo; Hafez, Mona Hafez; Shobokshy, Set A El; Wirtu, Gemechu (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Selenium (Se), as the form of selenite, is commonly supplemented in poultry diet, which has low bioavailability and high toxicity. Here, we compared the effects of the supplementation of the diet with Se nanoparticles (nano-Se) on the growth, sexual behavior, and reproductive performance (gonad size, sperm quality traits, and plasma testosterone levels for males and egg production for females) of Japanese quail (Coturnix coturnix japonica). Materials and Methods: Quail chicks (n = 300) aging 14 days were divided into three groups: Group 1 (basal diet and Se at 0.2 mg/kg ration), Group 2 (basal diet and nano-Se at 0.2 mg/kg ration), and Group 3 (basal diet and nano-Se at 0.1 mg/kg ration). Several parameters relating to body weight and egg were measured. Sexual behaviors of the birds were observed by continuous visual scanning. The sperm viability, sperm morphology, and concentration of spermatozoa were determined after staining and microscopic examination. The plasma testosterone levels were determined by indirect enzyme immunoassay assay. The Se concentrations in the testicular, ovarian, and ration samples were measured by flame emission atomic absorption spectrophotometer. Results: The type or concentration of nano-Se administration had no impact on body weight, feed efficiency, egg production, or egg weight. However, the total feed intake throughout the experiment was reduced in Group 2 at 0.2 mg/kg. Nano-Se supplementation significantly increased the sexual behavior. In general, the deposition of Se in the testicular and ovarian tissues increased with increasing supplement concentration. At the same supplement concentration, the tissue deposition of nano-Se was more enhanced than that of inorganic Se. Nano-Se supplementation improved the testicular functions by enhancing plasma testosterone level and sperm quality traits (sperm count, motility, and viability). This improvement was found more prominent with the lower supplement concentration (when comparing 0.1 vs. 0.2 mg/kg diet). Conclusion: It is concluded that the use of nano-Se (at 0.1 mg/kg) in the ration of Japanese quail improves several reproductive performance parameters. J. Adv. Vet. Anim. Res., 7(4): 597-607, Dec 2020 http://doi.org/10.5455/javar.2020.g457